Equivalent outcomes with minimally invasive and sternotomy mitral valve repair for degenerative mitral valve disease. Issue 8 (28th April 2021) - Bowdish, Michael E.; Elsayed, Ramsey S.; Tatum, James M.; Cohen, Robbin G.; Mack, Wendy J.; Abt, Brittany; Yin, Victoria; Barr, Mark L.; Starnes, Vaughn A.
Abstract: Background: Debate continues in regard to the optimal surgical approach to the mitral valve for degenerative disease. Methods: Between February 2004 and July 2015, 363 patients underwent mitral valve repair for degenerative mitral valve disease via either sternotomy (sternotomy, n  = 109) or small right anterior thoracotomy (minimally invasive, n  = 259). Survival, need for mitral valve reoperation, and progression of mitral regurgitation more than two grades were compared between cohorts using time‐based statistical methods and inverse probability weighting. Results: Survival at 1, 5, and 10 years were 99.2, 98.3, and 96.8 for the sternotomy group and 98.1, 94.9, and 94.9 for the minimally invasive group (hazard ratio: 0.39, 95% confidence interval [CI] 0.11–1.30, p  = .14). The cumulative incidence of need for mitral valve reoperation with death as a competing outcome at 1, 3, and 5 years were 2.7%, 2.7%, and 2.7% in the sternotomy cohort and 1.5%, 3.3%, and 4.1% for the minimally invasive group (subhazard ratio (SHR) 1.17, 95% CI: 0.33–4.20, p  = .81). Cumulative incidence of progression of mitral regurgitation more than two grades with death as a competing outcome at 1, 3, and 5 years were 5.5%, 14.4%, and 44.5% for the sternotomy cohort and 4.2%, 9.7%, and 20.5% for the minimally invasive cohort (SHR: 0.67, 95% CI: 0.28–1.63, p  = .38). Inverse probability weighted time‐based analyses based on preoperative cohort assignment also demonstrated equivalent outcomes between surgical approaches. Conclusions: Minimally invasive and sternotomy mitral valve repair in patients with degenerative mitral valve disease is associated with equivalent survival and repair durability.